Analysis of health care delivery systems: Pakistan versus United States - Saleem Punjani, Neelam; Shams, Salima; Bhanji, Sahreen Malik (International Journal of Endorsing Health Science Research, 2014)
Health plays an important role in shaping the human capital. Good health enhances the productivity and efficacy of the labor force which leads to the economic growth and human welfare. World health organization (WHO) has defined health system as “all organizations, people and actions whose primary intent is to promote, restore or maintain health". Healthcare delivery system is comprehensive therefore; for the analysis purpose; WHO health care system framework will be used. It has six building blocks which will be utilized as an instrument. The six blocks is comprised of leadership, human resource, information, medical products and technology, financing and service delivery. Intermediate output leads to the desired health outcomes. This paper presents the comprehensive analysis of the health care systems of Pakistan and United States America with the help of WHO health care system framework followed by health system challenges and concludes with some practical strategies to overcome those challenges.